2002
DOI: 10.1104/pp.007716
|View full text |Cite
|
Sign up to set email alerts
|

Function of a Plant Stress-Induced Gene, HVA22. Synthetic Enhancement Screen with Its Yeast Homolog Reveals Its Role in Vesicular Traffic

Abstract: Expression of the barley (Hordeum vulgare) HVA22 gene is induced by environmental stresses, such as dehydration, salinity, and extreme temperatures, and by a plant stress hormone, abscisic acid. Genes sharing high level of sequence similarities with HVA22 exist in diverse eukaryotic organisms, including animals, plants, and fungi, but not in any prokaryotic organisms. The yeast (Saccharomyces cerevisiae) HVA22 homolog, Yop1p, has been shown to interact with the GTPaseinteracting protein, Yip1p. Deletion of YOP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 40 publications
3
65
0
Order By: Relevance
“…It has been reported that the expression of barley (Hordeum vulgare) HVA22 is induced by several environmental stresses, such as dehydration, salinity, and extreme temperatures, as well as by a plant stress hormone, abscisic acid (Brands and Ho, 2002).…”
Section: Ccm-associated Genes Inmentioning
confidence: 99%
“…It has been reported that the expression of barley (Hordeum vulgare) HVA22 is induced by several environmental stresses, such as dehydration, salinity, and extreme temperatures, as well as by a plant stress hormone, abscisic acid (Brands and Ho, 2002).…”
Section: Ccm-associated Genes Inmentioning
confidence: 99%
“…Although both genes encode proteins with unknown functions, it has been shown that constitutive expression of HVA1 , which encodes a group 3 LEA protein, can confer drought resistance to transgenic plants (Xu et al, 1996). On the other hand, HVA22 probably is involved in intracellular vesicular trafficking (Brands and Ho, 2002). Promoter analyses of these two genes have demonstrated that two cis elements, an ACGT-box and a coupling element (together constituting ABA response complexes: ABRC3 in HVA1 and ABRC1 in HVA22 ), are necessary and sufficient for their induction by ABA (Shen and Ho, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The yeast homologue of RHD3, Sey1p, is a synthetic enhancer of Yop1p, whereas Yop1p and its conjunction protein Yip1p are integral membrane proteins that play a role in membrane traffic and endoplasmic reticulum-Golgi vesicle fusion. The protein Yip1p interacts with the Rab GTPases Ypt1p and Ypt31p/32p to regulate vesicle traffic in yeast (Yang et al 1998;Calero et al 2001;Brands and Ho 2002;Ortiz et al 2002;Barrowman et al 2003). Therefore, this implies that a role for RHD3 in facilitating Rab GTPase function in the Golgi in Arabidopsis could account for the diverse phenotypes in cell growth, endoplasmic reticulum-Golgi traffic, and vacuole organization (Zheng et al 2004).…”
Section: Discussionmentioning
confidence: 99%